Investigating the Role of Governance, Risk, and Compliance (GRC) in Investment Outcomes through Digital Transformation in Saudi Context - Alhamami, Mahdi; Alruwaili, Waleed S. (European Journal of Sustainable Development, 2025)
This study examines the impact of GRC on investments outcomes considering the role of digital transformation in Saudi context, given the research goals of exploring how this transformation affect this relation. The current research utilized a self-administrated questionnaire survey to collect the primary data. Using data drown from of 103 respondents, the research model was verified empirically in the context of Saudi Arabia. The findings revealed that GRC and digital transformation have exerted a significant influence on investment outcomes in Saudi context, suggesting that embedding GRC and digital transformation enhance investment outcomes and create a shareholders value. Policy wise, promoting an integrated GRC and digital transformation model is observed to be critical levers for institutional competitiveness in Saudi Arabia and beyond. This research furnishes timely evidence regarding GRC in the Saudi context and the ability of digital transformation to enhance investment outcomes across this region. Our study also contributes to the sustainable development discourse by exploring how digital transformation enhances GRC frameworks, thus improving investment outcomes in emerging markets such as Saudi Arabia, in alignment with global sustainability goals. Keywords: GRC, Digital Transformation, Investment outcomes, Saudi context